2018
DOI: 10.1016/j.fcr.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Yield stability of selected rice breeding lines and donors across conditions of mild to moderately severe drought stress

Abstract: Although mild to moderately severe drought stress may have less of an effect on rice grain yield than severe drought stress during reproductive stage, its prevalence across rice farmers’ fields at the global level may be more economically significant. In this study, field experiments were conducted on selected genotypes with known tolerance to severe reproductive-stage drought in order to identify those that would produce high and stable grain yield across seasons and soil moisture conditions varying from well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 23 publications
7
47
0
Order By: Relevance
“…Soil moisture tension during the stress was -47.83 kPa and -54.55 kPa in 2017 and 2018. Torres et al (2018) reported similar results of occurring moderate to severe stress when soil moisture tension drops below -50 kPa. Drought stress at vegetative stage reduces water content and lower leaf water potential, leading to reduce turgor, stomatal conductance, and photosynthesis, and ultimately reduce grain yield (Akbarian et al, 2011;Amini et al, 2014).…”
Section: Discussionsupporting
confidence: 52%
“…Soil moisture tension during the stress was -47.83 kPa and -54.55 kPa in 2017 and 2018. Torres et al (2018) reported similar results of occurring moderate to severe stress when soil moisture tension drops below -50 kPa. Drought stress at vegetative stage reduces water content and lower leaf water potential, leading to reduce turgor, stomatal conductance, and photosynthesis, and ultimately reduce grain yield (Akbarian et al, 2011;Amini et al, 2014).…”
Section: Discussionsupporting
confidence: 52%
“…The decrease in rainfall, increase in atmospheric CO 2 and more extreme weather events accompanied by a 1.5-4.5°C increase in temperature are expected in the next 100 years (Torres and Henry, 2016). Agriculture sector is severely affected by drought stress widespread in the arid and semi-arid area resulting in prominent loss of yield and production of agricultural crops.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the observed differences in postharvest ratoon tillering ability do not necessarily reflect differences in ratoon crop yield. Genotypes showing the highest levels of ratoon crop productivity included both relatively drought-susceptible as well as drought-tolerant released varieties based on previous evaluations (Torres & Henry, 2018). Interestingly, genotypes Binuhangin and IR87707-445-B-B-B (released as the variety DRR 42 in India) have both stood out as having high grain yield under drought in previous reports (Swamy et al, 2013;Torres, McNally, Vera Cruz, Serraj, & Henry, 2013) and have shown some similarities in their physiology in terms of low canopy temperature and deep root growth compared with other genotypes (Henry et al, 2015;Torres & Henry, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To characterize postharvest ratooning, two sets of genotypes ( Supplemental Table S1) were selected from drought screening trials in the 2012 dry season (DS) (reported by Torres & Henry, 2018) based on their contrasting yield under drought (the "drought resistance" set) or their contrasting ratooning ability (the "ratooner" set), which was assessed after harvest of the trial. Separate experiments on postharvest ratooning were conducted on these two sets of genotypes in two consecutive dry seasons and wet seasons (WS) from 2013WS to 2015DS.…”
Section: Postharvest Ratooning After Main Crop Well-watered and Drougmentioning
confidence: 99%